Epidemiology of Stenocarpella macrospora (Earle) Sutton on maize in the midaltitude zone of Nigeria - Olatinwo, R.O.; Cardwell, K.F.; Deadman, M.L.; Julian, A.M. (1999)
Disease progress of Stenocarpella macrospora (Earle) Sutton (syn. Diplodia macrospora Earle) was monitored on selected maize breeding lines over two seasons at three locations. Tagged plants were assessed at 10 day intervals for foliar lesions on a 1–9 scale and for ear rot on a 1–5 scale. The level of disease at a farm in Jos (West Africa Milk Company farm) was significantly greater than those at the other two locations (UTC Tenti and Saminaka), which had reduced or zero debris from the previous year's cultivation. There was a significant correlation between the leaf severity score and grain weight, where grain weight decreased with increasing leaf disease severity. However, no significant correlation was observed between ear rot and leaf severity. Varieties responded differently throughout the monitoring period. Late planting (1996) resulted in a significantly reduced disease incidence, but also resulted in lower grain weights. Spatial disease progress diagrams indicated that S. macrospora was initiated from random foci from which secondary spread occurred.